Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1071/wf10055
|View full text |Cite
|
Sign up to set email alerts
|

Wind - terrain effects on the propagation of wildfires in rugged terrain: fire channelling

Abstract: The interaction of wind, terrain and a fire burning in a landscape can produce a variety of unusual yet significant effects on fire propagation. One such example, in which a fire exhibits rapid spread in a direction transverse to the synoptic winds as well as in the usual downwind direction, is considered in this paper. This type of fire spread, which is referred to as ‘fire channelling’, is characterised by intense lateral and downwind spotting and production of extensive flaming zones. The dependence of fire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
124
1
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 111 publications
(158 citation statements)
references
References 21 publications
14
124
1
4
Order By: Relevance
“…3c, 2.5 h earlier. The lateral fire propagation evident at GV-N is consistent with and best explained by the fire channelling phenomenon discussed by Sharples et al (2012). Indeed, the steep lee slopes of the numerous side spurs leading north to Carmarthen Ridge satisfy the preconditions necessary for fire channelling to occur .…”
Section: Fire Channelling Banks Ridge 22 Novembersupporting
confidence: 54%
See 1 more Smart Citation
“…3c, 2.5 h earlier. The lateral fire propagation evident at GV-N is consistent with and best explained by the fire channelling phenomenon discussed by Sharples et al (2012). Indeed, the steep lee slopes of the numerous side spurs leading north to Carmarthen Ridge satisfy the preconditions necessary for fire channelling to occur .…”
Section: Fire Channelling Banks Ridge 22 Novembersupporting
confidence: 54%
“…In their analysis of the 2003 Canberra bushfires, Sharples et al (2012) demonstrated several cases where interactions between strong winds and rugged topography resulted in rapid wildfire development. The resulting process, which they termed "fire channelling", resulted in a transition from the usual frontal burning pattern to an areal burning pattern caused by a combination of rapid lateral fire propagation (transverse to the prevailing winds) and downwind infill by short-to medium-range spotting.…”
Section: R H D Mcrae Et Al: Linking Local Wildfire Dynamics To Pymentioning
confidence: 99%
“…Fire severity in these areas was primarily influenced by weather conditions on the day of the fire than by their physical and topographic properties. It is likely that the highly variable nature of fire weather was responsible for the range of fire severity responses observed across these moderate predicted classes (Bradstock et al 2010, Price and Bradstock 2012, Sharples et al 2012.…”
Section: Discussionmentioning
confidence: 99%
“…Fire occurrence is favoured by low humidity and high temperature, whereas wind speed has long been recognised as the crucial factor influencing the rate of spread of wildfires (Rothermel 1972;Fosberg 1978). In addition, interactions of fuels and weather with local topography can greatly influence fire activity (Moritz et al 2010;Sharples et al 2012). Fire behaviour models incorporate information on fuels, topography and weather to predict fire spread (Sullivan 2009a(Sullivan , 2009b(Sullivan , 2009c.…”
Section: Discussionmentioning
confidence: 99%